Relationship between cardiac autonomic regulation and auditory mechanisms: Importance for growth and development - Valenti, Vitor Engrácia [UNESP] (2013)
The literature has already demonstrated that auditory stimulation with music influences the cardiovascular system. In this study, we performed a literature review in order to investigate the relationship between auditory mechanisms and cardiac autonomic regulation. The selected studies indicated that there is a strong correlation between noise intensity and vagal-sympathetic balance. Also, it was reported that music therapy improved heart rate variability in anthracycline-treated breast cancer patients. It was hypothesized that dopamine release in the striatal system induced by pleasure songs are involved in the cardiac autonomic regulation. Further studies are necessary to add new elements in the literature to improve new therapies to treat cardiovascular disorders.